Elucidating the Fusarium graminearum species complex on maize in South Africa - Pretorius, A. (North-West University, 2018)
Maize is one of the most important grain crops in South Africa as it serves as the staple diet of millions of people. The increasing populations and demand for food crops are not the only constraint of cereal production, an average percentage of 10-30% is lost due to fungal infections. Fusarium graminearum species complex (FGSC) is the most global complex causing diseases on various grain crops worldwide. FGSC causes diseases on maize such as Gibberella ear-, stalk-, root- and crown rot. This species complex can cause yield losses in crops of up to 70%. Recent studies indicated the increasing FGSC levels in South Africa. Biotic constraints on maize such as stem borers can also cause wounds which provides entry points for fungal infection. Furthermore, the infection of FGSC members poses a health threat for humans and animals as this species complex produce secondary toxic metabolites known as mycotoxins. The most common mycotoxins include, zearalenone (ZEA), deoxynivalenol (DON) and nivalenol (NIV). Thus, the importance of monitoring diseases in crops is emphasised and the prediction of disease epidemics lies in the proper identification, management and understanding of genetic diversity and population biology. Fungal identification are fundamental requirements when managing or studying diseases caused by FGSC members. Molecular techniques based on analysis of DNA such as polymerase chain reaction (PCR), species-specific PCR and PCR- restriction fragment length polymorphism (PCR-RFLP) were therefore evaluated to identify FGSC members on diseased maize. Multilocus genotyping (MLGT) were used to evaluate the accuracy of the PCR-based techniques. MLGT were able to identify two new species on maize, F. lunulosporum and F. cerealis, this is also a first report of these two species on maize. A hybrid species, F. graminearum x F. boothii was also detected in these samples using the MLGT technique. To study plant part preference by FGSC members, the pathogenicity, colonisation and mycotoxin production of three FGSC members (F. graminearum, F. boothii, F. graminearum x F. boothii) collected from diseased maize were tested by the artificial inoculation on maize stems and ears in glasshouse conditions. Fungi are not just able to be pathogenic in maize- ears, roots and crowns, but showed in this study that fungi can also successfully infect maize stems. Different mycotoxins such as zearalenone and nivalenoland was produced in different levels by the isolates in different plant parts. Natural occurring FGSC members in field conditions occurring during the growing season of 2016/17 were evaluated in Vaalharts and Potchefstroom, as well as the possible relationship with natural occurring maize stem borer on maize. A trend of FGSC members in maize stems for all three cultivars was noted in Vaalharts and Potchefstroom, the most vulnerable stage of maize growth is at 70 days when the plant is busy with grain fill.
Masters in Environmental Science, North-West University, Potchefstroom Campus
Keywords: Fusarium graminearum species complex; polymerase chain reaction; pathogenicity; mycotoxins; stem borers